ANALISIS UNSUR BIAYA PRODUKSI DAN ALOKASI BIAYA BERSAMA PADA BATIK TRADISIKU BOGOR - Septiani, Delina Herdian; Sahara, Nis Putri Sheila Nur; Amelia, Riska; Hardiansyah, Yera (Jurnal Riset Terapan Akuntansi, 2025)
Batik Tradisiku is a small and medium-sized enterprise (SME) that produces batik fabric as it’s the main product. This study aims to analyze the components of production costs comprehensively as the basis for determining the cost of goods sold (COGS) and selling price. A descriptive method was employed, with data collected through observation and interviews. The results indicate that Batik Tradisiku Bogor has recorded production costs accurately by including all relevants cost elements,resulting in optimal business revenue and profit. In addition, the study found the presence of joint costs that need to be allocated separately. The market value proved to be the most appropriate approach for allocating actual production costs, as it leads to a lower COGS compared to the selling price. The results of this study are expected to support more efficient business decision-making and enhance the market competitiveness of batik fabric production in Indonesia. Keywords: Joint Cost Allocation, Cost of Production, Cost of Goods Sold